Democracies in crisis: Public policy responses to the Great Depression - "Hill , Kim Quaile" (London, 1988)
This book explains many of the separate components of policy revolution. One of the most critical aspects is concerned government's success in attempting to resolve the depression. There is no scholarly consensus-indeed, there is extraordinary controversy-about what governments actually attempted by way of ameliorative policy efforts and what was achieved thereby. Despite an enormous amount of scholarly attention, these important matters remain unsettled.
Keywords: Democracies